[SWI(+)], the Prion Formed by the Chromatin Remodeling Factor Swi1, Is Highly Sensitive to Alterations in Hsp70 Chaperone System Activity - Hines, Justin K. (Public Library of Science, 2011)
The yeast prion [SWI(+)], formed of heritable amyloid aggregates of the Swi1 protein, results in a partial loss of function of the SWI/SNF chromatin-remodeling complex, required for the regulation of a diverse set of genes. Our genetic analysis revealed that [SWI(+)] propagation is highly dependent upon the action of members of the Hsp70 molecular chaperone system, specifically the Hsp70 Ssa, two of its J-protein co-chaperones, Sis1 and Ydj1, and the nucleotide exchange factors of the Hsp110 family (Sse1/2). Notably, while all yeast prions tested thus far require Sis1, [SWI(+)] is the only one known to require the activity of Ydj1, the most abundant J-protein in yeast. The C-terminal region of Ydj1, which contains the client protein interaction domain, is required for [SWI(+)] propagation. However, Ydj1 is not unique in this regard, as another, closely related J-protein, Apj1, can substitute for it when expressed at a level approaching that of Ydj1. While dependent upon Ydj1 and Sis1 for propagation, [SWI(+)] is also highly sensitive to overexpression of both J-proteins. However, this increased prion-loss requires only the highly conserved 70 amino acid J-domain, which serves to stimulate the ATPase activity of Hsp70 and thus to stabilize its interaction with client protein. Overexpression of the J-domain from Sis1, Ydj1, or Apj1 is sufficient to destabilize [SWI(+)]. In addition, [SWI(+)] is lost upon overexpression of Sse nucleotide exchange factors, which act to destabilize Hsp70's interaction with client proteins. Given the plethora of genes affected by the activity of the SWI/SNF chromatin-remodeling complex, it is possible that this sensitivity of [SWI(+)] to the activity of Hsp70 chaperone machinery may serve a regulatory role, keeping this prion in an easily-lost, meta-stable state. Such sensitivity may provide a means to reach an optimal balance of phenotypic diversity within a cell population to better adapt to stressful environments.